Pemberdayaan Ibu-Ibu PKK Melalui Pelatihan Pembuatan Getuk Premium Untuk Meningkatkan Perekonomian Rumah Tangga - Muhammad Ali Muhtarom; Rofi Kurnia Hakim; Khoiriyatus Sa’adah; Aldiva Merediana Arkharajma Putri; Umi Qoni'ah; Sri Muafifah; Afifah Nadilla; Ajeng Gayska Rahmanita; Ani Lutviana; Aprylia Yuvitasari; Julia Ambarwati; Nailul Izzah (Najah Bestari, 2024)
Community empowerment programs, especially for women, have become an important focus at the local level to reduce poverty levels and increase household economic independence. In this article, we will discuss the results of a project that aims to encourage Family Welfare Empowerment (PKK) women at the local level to take part in economic endeavors through training in making premium getuk as an alternative business. This research involved PKK women from Mataram Jaya village, Bandar Mataram subdistrict, Central Lampung district. This service uses the ABCD approach, or assets, potential, strengths, and maximum utilization. The basic concept for ABCD asset-based community development is as follows: Half-filled is more significant, each asset has potential, participation, collaboration, positive deviation, comes from society in general, and leads to energy sources. Ef orts such as this premium getuk making training show great potential to empower women at the local level and improve the overall economic welfare of the community in the context of inclusive and sustainable economic development. This study shows that investment in training and skills development is critical to fighting poverty and creating broader economic opportunities for communities.